Home advantage and referee bias: A comparative analysis of league level differences - Isin, A. (Perceptual and Motor Skills, 2023)
Home advantage (HA) and referee bias are two important phenomena in football (soccer) and are frequently investigated by researchers. This study focused on analyzing HA and referee bias at different league levels. The study included 632 matches played in Turkey`s top two leagues during the 2022-2023 season. Both leagues showed statistically significant game outcome differences between home and away teams regarding points, goals, shots, shots on target, passes, accurate passes, and ball possessions, indicating a HA. However, regarding referee bias, this study found that only Level 1 teams significantly differed in penalties and that this difference was not evident after analyzing for Bayes factors. Among Level 2 teams, as there was no statistical difference between home and away teams on any parameter indicating referee bias, and all Bayes factors indices were between 3.92-11.15, the null hypothesis was supported. Therefore, the results revealed a HA at both league levels, but a referee bias was not present in either league. This study emphasized that the HA phenomenon is clear and still evident in elite football and sub-elite leagues.